HMG1 interacts with HOX proteins and enhances their DNA binding and transcriptional activation. - Zappavigna, V (1996)
High mobility group protein 1 (HMG1) is a non-histone, chromatin-associated nuclear protein with a proposed role in the regulation of eukaryotic gene expression. We show that HMG1 interacts with proteins encoded by the HOX gene family by establishing protein-protein contacts between the HMG box domains and the HOX homeodomain. The functional role of these interactions was studied using the transcriptional activity of the human HOXD9 protein as a model. HMG1 enhances, in a dose-dependent fashion, the sequence-specific DNA binding activity in vitro, and the transcriptional activation in a co-transfection assay in vivo, of the HOXD9 protein. Functional interaction between HMG1 and HOXD9 is dependent on the DNA binding activity of the homeodomain, and requires the HOXD9 transcriptional activation domain. HMG1 enhances activation by HOXD9, but not by HOXD8, of the HOXD9-controlled element. Specific target recognition and functional interaction with HMG1 can be transferred to HOXD8 by homeodomain swapping. We propose that HMG1-like proteins might be general co-factors in HOX-mediated transcriptional activation, which facilitate access of HOX proteins to specific DNA targets, and/or introduce architectural constraints in the assembly of HOX-containing transcriptional complexes.